PENGARUH ECONOMIC VALUE ADDED (EVA), PROFITABILITAS DAN LEVERAGE TERHADAP RETURN SAHAM DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Muhsin N Bailusy; Fadlli Ali Taslim (Jurnal Manajemen Sinergi, 2019)
This study aims to determine the effect of Economic Value Added(EVA), Profutability and Leverage on Stock Returns with Company Valueas an Intervening Variable. In the consumer goods industry sector listed on the Indonesia Stock Exchange in 2013-2017. The results of this studyindicate that the direct effect of economic value added (EVA) variablesdoes not affect stock returns, profitability variables (ROE) do not affectstock returns, leverage variables (DER) do not affect stock returns andfirm value variables (PBV) have no effect on stock returns. While theindirect effect of firm value (PBV) mediates the effect of economic valueadded (EVA) on stock returns, firm value (PBV) cannot mediate theeffect of profitability (ROE) on stock returns and firm value (PBV) cannotmediate the effect of leverage (DER) ) of stock returns.